Metabolic engineering of plant secondary metabolites: prospects and its technological challenges - Mipeshwaree Devi, Asem; Khedashwori Devi, Khomdram; Premi Devi, Pukhrambam; Lakshmipriyari Devi, Moirangthem; Das, Sudripta (Frontiers in Plant Science, 2023)
Plants produce a wide range of secondary metabolites that have important roles for their primary functions such as growth, defence, adaptations or reproduction. Some of the plant secondary metabolites are beneficial to mankind as nutraceuticals, pharmaceuticals, etc. Metabolic pathways and their regulatory mechanism are crucial for targeting metabolite engineering. The clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9-mediated system has been widely applied in genome editing with high accuracy, efficiency, and multiplex targeting ability. Besides its vast application in genetic improvement and germplasm innovation, the technique also facilitates a comprehensive profiling approach to functional genomics related to gene discovery involved in various plant secondary metabolism. Despite these wide applications, several challenges limit CRISPR/Cas system application in genome editing in plants. This review highlighted updated applications of CRISPR/Cas system-mediated metabolic engineering of plants and its challenges.